Capabilities and mechanisms of microalgae on nutrients and florfenicol removing from marine aquaculture wastewater. (15th October 2022) - Qian, Zhang; Na, Li; Bao-Long, Wang; Tao, Zhang; Peng-Fei, Ma; Wei-Xiao, Zhang; Sraboni, Nusrat Zahan; Zheng, Ma; Ying-Qi, Zhang; Liu, Ying
Abstract: The regulations governing the discharge of marine aquaculture wastewater are becoming increasingly stringent, and the problems of nitrogen and phosphorus pollution and antibiotic residues in wastewater are serious. Microalgae-based treatment with the dual benefits of wastewater purification and microalgae resource recycling was regarded as the most promising technology in aquaculture wastewater treatment. Isochrysis galbana and Chlorella sp. were chosen to investigate antibiotic and nutrient removal mechanisms from aquaculture wastewater. FLO addition stimulated microalgae growth at low FLO concentrations (0.1 and 1 mg/L) but inhibited growth at 10 mg/L. The removal efficiency of DIN by Chlorella sp . and I. galbana after 7 days of cultivation was 66.4% and 25.8%, respectively. Linear curves were obtained between DIN concentration and cultivation duration, remove constant ( k ) increased as FLO concentration increased from 0 to 10 mg/L, and the highest value of k was obtained in both the Chlorella sp. and I. galbana groups at 10 mg/L. DIP concentrations in FLO-contained simulated aquaculture wastewater decreased sharply with the cultivation of Chlorella sp. and I. galbana, and DIP removal rate increased as FLO concentration increased. When the initial concentration of FLO was 0.1 mg/L, biodegradation by I. galbana accounted for 86.67% of FLO removal. In contrast, FLO removal with biodegradation and biosorption by Chlorella sp . was 89.74% and 3.72%, respectively. Furthermore, Chlorella sp. grown in MPBR demonstrated superior capability for antibiotic-containing marine aquaculture wastewater purification, with average removal rates of DIN and DIP of 81.2% and 100%, respectively. The high removal rate is related to membranes which can improve microalgae performance by decoupling SRT and HRT. For microalgae-based aquaculture wastewater, ammonia was the most crucial nitrogen source, followed by nitrate. These findings serve as a theoretical foundation for developing microalgae-based aquaculture wastewater treatment technology and eliminating antibiotics in aquaculture. Graphical abstract: Image 1 Highlights: Chlorella sp. outperformed in nutrient removal efficiency and florfenicol tolerance. Ammonia was the most crucial nitrogen source, followed by nitrate. Biodegradation is the principal pathway for florfenicol removal by microalgae. Chlorella sp. in membrane photobioreactor had potential for wastewater purification.